Pedagogia poiética para a potência humana : o reconhecimento, a nutrição e a expansão da potência humana das comunidades aprendentes, em processos poiéticos colaborativos de reorientação curricular pedagógica cultural, e as tecituras transdisciplinares das alfabetizações de mundos em rodas de conversações - Trindade, Ana Felícia Guedes (2015)
This thesis defends human potency. From the potency of human nature to humanities in its potent movements. The potency defended in this study is recognized from complex organicbiological- cultural reorganizations produced in movements of autopoiesis(Maturana,1979) which are weaved mainly in historical and social, philosophical and anthropological, psychological and aesthetic circumstances, which are forged in the multiple dimensions of a human being's life and are entwined and developed, nurtured both by autopoietic and by bioanthro- poetic processes (Morin,1990). From this complex production, human beings exercise the organization and the disorganization of identities and authorships in which autonomy, as life production (Freire, 1979) is generated and gestated. This deeply complex and autopoietic production, which constitutes the being, nurtures human potency, which expands and strenghtens in human processes. The present thought, produced by approaching these three authors from distinct scientific schools and complemented by other authors in the realm of human and social sciences, constitutes the theoretical-practical basis for the research conducted at Escola Municipal de Ensino Fundamental Erna Würth, Canoas/RS, a participative and collaborative action-research called "Poietic Pedagogy for Human Potency".The research is a proposal of exercises of teaching potency, in conversation circles as continuing education, in a productive workfield, considering the nurturing and the viewing of learning and teaching processes, by recognizing students' potencies. The conversation circles generate, through meditated conversations, the Letter of Principles, the Worlds Literacies, the Webs of Life and the Orienting Threads – collaborative pedagogical-poietical webbings which constitute today the pedagogical-cultural planning construction of the learning community.